Changes in age-sex mortality patterns and causes of death in the Republic of Korea - Tai-Hun Kim (Asia-Pacific Population Journal, 2005)
The high population growth in many developing countries is caused by relatively low mortality and continuing high fertility. Under those circumstances, it is difficult to deny that reducing fertility is crucial for curbing rapid population growth. Nonetheless, because the health status of a population has an obvious bearing on mortality, its importance as a variable affecting the quality of the population has also been recognized (United Nations, 1973, p. 107). Therefore, while fertility reduction is an important factor for curbing population growth rates, mortality (or health) control is required for improving the quality of the population.